2017
DOI: 10.3390/ijerph14121549
|View full text |Cite
|
Sign up to set email alerts
|

Practicing Dentists’ Self-Efficacy and Associated Factors in Managing the Treatment of Adults with Mental and Physical Disabilities: An Exploratory Cross-Sectional Study in Riyadh, Saudi Arabia

Abstract: Background: Provision of oral healthcare to adults with mental and physical disabilities (AMPD) remains a challenging area across various healthcare systems. The present study aimed to assess self-reported efficacy and investigate factors associated with self-efficacy in the management of AMPD among practicing dentists in Saudi Arabia. Methods: A pilot-tested, self-administered questionnaire was distributed to a convenience sample of 1000 dentists. Descriptive and inferential analyses were performed on the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… 15 Besides, another study reported relatively lower SE among 1000 dentists when treating adult patients with mental and physical disabilities. 18 Studies in Norway and United States exhibited improved SE among doctors after completing a communication skills training course. 27 , 28 On the other hand, marital status, smoking, and regular exercise showed no significant relationship with the level of SE among HCWs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Besides, another study reported relatively lower SE among 1000 dentists when treating adult patients with mental and physical disabilities. 18 Studies in Norway and United States exhibited improved SE among doctors after completing a communication skills training course. 27 , 28 On the other hand, marital status, smoking, and regular exercise showed no significant relationship with the level of SE among HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…For every study participant, the following data were collected through a self-administered questionnaire that included the following sections: Socio-demographic, health, and occupational characteristics; The following variables were adopted from previous studies with some modifications. 12 , 16 , 18 Age, gender, nationality, smoking status, chronic health condition, history of anxiety and/or depression, profession, hospital type, Corona team membership, experience, years of experience and working hours per day were inquired about. WHO five Well-Being Index (WHO-5): This scale was used to assess the current mental well-being over the last two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Al Qahtani et al in their observational study assessed the self-reported efficacy of Saudi Arabian dentists and investigated factors associated with self-efficacy in the management of adults with mental and physical disabilities. 31 Compared to the present study, which has an experimental design, the study of Al Qahtani et al does not have similar data or approach to make a comparison.…”
Section: Discussionmentioning
confidence: 57%
“…In the dental literature, there are a limited number of publications studying the effect of self-efficacy on clinical performance. [13][14][15]31,32 Opacic investigated the predictive relationship between student physician assistants' self-efficacy beliefs and their clinical performance. 9 Three hundred students from 14 accredited programs who were in the first year of their clinical professional education were involved in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation